Female Pastors in Protestant Communities in Ukraine: A View on Gender Roles and Their Own Status in the Community - Dudko,Yeliena (2018)
Collapse of the Soviet Union and abolishment of the state atheism policy has led to an increase of Protestant organizations and their parishes in Ukraine. Some of them (at least fifteen) allow and practice women ordination. Women priests, thus, find themselves performing non-traditional gender roles in Ukraine, where the majority of the population is affiliated with Orthodox or Greek Catholic Churches that at the moment deny female ordination. Firstly, this thesis outlines the main debates on female ordination, as well as reviews the research about female pastors in Western countries. Secondly, it provides statistical data about denominations that allow female ordination in Ukraine. Thirdly, based on the half-structured in-depth interviews this explorative study discusses the lived experiences of women priests in Ukraine. It discusses how they view their status in their community and society and whether they experience gender discrimination in their work. It also analyzes the attitudes of female pastors towards ideas of feminism and gender equality.
Keywords: Gender Equality; Ordination; Feminism